Voltage-gated proton channel Hv1/VSOP regulates reciprocal interactions between F-actin and endosomes in microglia - Takafumi Kawai; Daisuke Yoshioka; Pattama Wiriyasermkul; Risa Mori-Kreiner; Rizki Tsari Andriani; Megumi Kobayashi; Manabu Abe; Kenji Sakimura; Kazuki Nagayasu; Shushi Nagamori; Yasushi Okamura (Proceedings of the National Academy of Sciences, 2026)
Voltage-gated proton channel Hv1/VSOP has long been regarded as a plasma membrane protein that modulates intracellular pH and membrane potential to support immune cell function. Here, we reveal an unexpected intracellular pool of Hv1 on endosomal membranes in microglia, where it orchestrates a reciprocal interplay between endosomal trafficking and the actin cytoskeleton. Combining endosome patch-clamp recordings with high-resolution imaging, we demonstrate that functional endosomal Hv1 forms tight and dynamic associations with F-actin. Genetic deletion of Hv1 markedly elongates actin filaments, a phenotype that appears to depend on intracellular rather than plasma membrane Hv1 activity. Heterologous expression of wild-type Hv1, but not a proton-non-conducting mutant, reduced the F-actin staining, indicating that the ion-conducting function is required for this regulation. Live-cell imaging reveals that Hv1-positive endosomes move in concert with F-actin networks and frequently engage with their terminal regions, suggesting that filament barbed ends are trapped at Hv1-positive endosomes. Proximity-labeling proteomics identifies the actin-capping protein CAPZ as a critical mediator of Hv1-dependent actin remodeling, and genetic ablation of CAPZ abolishes the actin phenotype in Hv1-deficient microglia. These findings uncover a previously unrecognized ion channel–cytoskeleton crosstalk that shapes endosomal function and microglial physiology, redefining the functional landscape of voltage-gated proton channels.